Centennial Lecture The Relationship of Parliament and the Courts: A Tentative Though or Two for the New Millennium - Thomas, E W (Victoria University of Wellington Law Review, 2000)
This paper was delivered as the Victoria University of Wellington Law Faculty's Centennial Lecture on 30 June 1999. The author discusses the principle of Parliamentary Sovereignty, and the question as to whether the judiciary must acknowledge Parliament's sovereign legislative power without qualification. It is suggested that Parliament's legislative supremacy is not absolute, and that the courts have a crucial role in enforcing rights. However, the author also stresses that the fundamental plank of the constitution is the sovereignty of the people, and that Parliament's democratic imperative is representative government.